Analysis of Information Technology Governance Using the COBIT 5 Framework (Case Study: E-Legal Drafting Legal Section of the Regional Secretariat of Salatiga City) - Caecilia Ika Pramita Ady; Prihanto Ngesti Basuki; Augie David Manuputty (Universitas Bina Darma, 2019)
Information Technology (IT) governance is used to manage and optimize IT resources in supporting organizational goals. The Legal Section of the Regional Secretariat of Salatiga City as part of a government organization has built E-Legal Drafting information system to develop the functions of making regional legal products as well as the realization of e-government development in the legal field. The COBIT framework supports IT governance by providing work support to regulate IT alignment with the organization's business objectives. The results of this study are expected to show an overview of the implementation of IT governance in E-Legal Drafting information system from APO domain within the COBIT 5 framework, show the current system information level of capability and performance that is obtained from the measurement of capability levels, and also providing evaluation and recomendation based on the results of the gap analysis to help obtain the quality of information systems expected by the Legal Section of the Regional Secretariat of Salatiga City.